Registro de la actividad eléctrica cerebral de la atención implicada en la conducción bajo el efecto del alcohol usando un instrumento bci (brain control interface) (2015)
The ingestion of alcohol has been linked to characteristic changes in EEG activity, and these changes depend on several factors. Previous research has been conducted with a variety of experimental designed, but most have focused on reporting the effect of alcohol consumption in subjects with a history of alcohol abuse, and a few have reported the effects of lower doses of alcohol. This project recorded brain activity related to attention in a driving situation with an emotiv EPOC brain control interface (BCI) device after ingestion of 0,300 g of alcohol (0,02 % bac) or none in a preexperiemental pre-test and post-test design with 30 college students aged 18-45. Results suggest that lower doses of alcohol change wave dynamics, reducing the amplitude of fast alpha (9-13Hz) and beta (14-30Hz) waves in frontal lobe zones involved in sustained attention in driving.